Examination of Age-Related Retinal Vascular Changes in the Macula Using Optical Coherence Tomography Angiography of the Eyes After Cataract Surgery - Yoshikawa Y (Dove Medical Press, 2021)
Yuji Yoshikawa, Takuhei Shoji, Junji Kanno, Hisashi Ibuki, Kimitake Ozaki, Hirokazu Ishii, Hiromi Inami, Kei Shinoda Department of Ophthalmology, Saitama Medical University, Iruma, Saitama, JapanCorrespondence: Kei ShinodaDepartment of Ophthalmology, Saitama Medical University, 350-0495 Morohogo 38, Iruma, Saitama, JapanTel +81 49-276-1250Fax +81 49-295-8002Email shinodak@med.teikyo-u.ac.jpPurpose: Optical coherence tomography angiography (OCTA) allows noninvasive observation of the retinal vasculature, and image analysis can be used to calculate the retinal vessel density and foveal avascular zone (FAZ) area. A previous study showed that macular vessel density and the signal strength index (SSI) of OCTA images increased significantly after cataract surgery. However, the effect of aging on OCTA analysis remains unclear. This study aimed to investigate age-related changes in macular vascularization while excluding the effects of cataracts.Patients and Methods: OCTA imaging of the macula was performed in adult patients who had undergone cataract surgery between February 2018 and May 2019 and in young healthy participants between April 2017 and April 2018.Results: The median (quartiles) age of the overall study population was 59.0 (27.0, 69.0) years, and no severe refractive error was observed (axial length: 24.2 ± 1.3 [mean ± SD] mm; spherical equivalent: 0.75 [− 2.25, 0.00] diopter). When we investigated the relationship between macular vessel density and age after excluding the effects of cataracts, we found that the macular vessel density showed age-related changes even in the absence of the effects of the SSI. However, the FAZ area was not affected by age.Conclusion: Macular vessel density decreased with age, even when the effects of cataracts were excluded. The effects of age and cataracts should be considered when designing studies and interpreting OCTA findings of the retinal vasculature.Keywords: optical coherence tomography angiography, macular vessel density, foveal avascular zone, aging, cataract surgery